Estimation of G-quartet-forming guanines in parallel-type G-quadruplexes by optical spectroscopy measurements of their single-nucleobase substitution sequences. Issue 17 (9th August 2018) - Maruyama, Ryo; Makino, Kurumi; Yoshitomi, Toru; Yui, Hiroharu; Furusho, Hitoshi; Yoshimoto, Keitaro
Abstract : Here, we established a new estimation method for G-quartet-forming guanines in parallel-type G-quadruplexes using measurements of circular dichroism and thermal stability. Abstract : Since much attention has been paid to in vivo biological functions of G-quadruplexes, structural analyses of G-quadruplexes are essential for understanding their functional mechanisms. Here, we established a simple optical-spectroscopy-based method for the estimation of G-quartet-forming guanines in parallel-type G-quadruplexes using measurements of circular dichroism and the thermal melting temperature.